POLYSEMY, POLYVALENCE, AND LINKING MISMATCHES: THE CONCEPT OF RAIN AND ITS CODINGS IN ENGLISH, GERMAN, ITALIAN, AND SPANISH - Zaefferer, Dietmar (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
Based on an ontological frame for comparative onomasiological lexicology which embeds the RAIN eventity type as an exponent-shaped activity into a general linguistic ontology as well as an ontology of motion, the words for RAIN in two Germanic and two Romance languages are compared with respect to their semantic and syntactic variability. It turns out that the Germanic forms are more flexible than the Romance forms. English rain has the highest variability: It can be used with eight valencies, a nominal and seven verbal ones, and with five different meanings, and it is the only one to display a valence that combines an expletive subject with a cognate object as well as a causativized eventity meaning. On the other hand only German regnen has a resultativized meaning. The Romance languages too show some internal variance: In allowing both an impersonal construction with a generalized meaning and a source construction, Spanish llover is slightly more flexible than Italian piovere. Finally, an Optimality Theoretic account of the data is adumbrated in terms of three principles: Avoid linking mismatches, Avoid heterogeneity of sentence patterns, and Avoid redundancy.